PENYULUHAN PENENTUAN KESUBURAN TANAH DI LAPANGAN DAN HASIL ANALISIS LABORATORIUM DALAM MENENTUKAN KUALITAS TANAH DI DESA KERSAMENAK, TAROGONG KIDUL, GARUT - Henly Yulina; Wiara Sanchia Grafita Ryana Devi; Fadhillah Laila; Farida Mardatila (Jurnal Abdi Inovatif : Pengabdian kepada Masyarakat, 2024)
The decline in rice yields is a problem that is often experienced by farmers. The problem had experienced by the Mukti Tani III Farmer Group in Kersamenak Village, Tarogong Kidul District, Garut Regency was decrease rice production due to decreased soil quality and excessive use of fertilizers that are not adapted to plant needs. The aim of this activity was introduced and increased farmers' understood of how to determined soil fertility in the field and identified the results of soil analysis in the laboratory in determining soil quality, how to apply soil fertility determination methods in the field, and soil identifiers in the category of healthy, moderate or dificiency. So that the need for fertilizer could be determined according to the needs of the plant. The methods used are counseling, discussion, and evaluation. Activities are carried out in several stages. The first stage was coordinating and socializing with the Kersamenak Village government and conducting Focus Group Discussion (FGD) activities and filling out the pre test. The second stage is discussion (question and answer), and the third stage is evaluation through filling out the post test. The results of the evaluation showed that the technique for determining soil fertility in the field and the results of soil analysis in the laboratory became a solution for the Mukti Tani III Farmers Group in regulating the application of fertilizer so that it does not add too much fertilizer to the soil, so that rice plant growth is more optimal. From the results of the pre-test and post-test questionnaires, there was an average increase in general knowledge about how to determine soil fertility by 21.72%. Knowledge of how to determine soil fertility in the field increased 39.13% and knowledge of how to determine soil fertility in the laboratory increased 26.09%. This shows that the extension activities that have been carried out have had a positive impact in increasing farmer knowledge about how to determine soil fertility in the field and identification the results of analysis in the laboratory to improve soil quality. Keywords: soil fertility, productivity, physical properties, chemical properties of soil Abstrak Penurunan produksi padi merupakan masalah yang sering dihadapi petani. Permasalahan kelompok tani Mukti Tani III di Desa Kersamenak, Kecamatan Tarogong Kidul adalah penurunan hasil padi akibat kualitas tanah serta penggunaan pupuk berlebihan yang tidak disesuaikan dengan kebutuhan tanaman. Tujuan pengabdian kepada masyarakat ini adalah untuk mengenalkan dan meningkatkan pemahaman petani tentang cara menentukan kesuburan tanah di lapangan dan mengidentifikasi hasil analisis tanah di laboratorium untuk menentukan kualitas tanah. Metode yang dilakukan adalah penyuluhan dengan ceramah, Focus Group Discussion FGD, dan evaluasi dengan metode tes, yaitu membandingkan hasil pre-test dan post-test. Kegiatan tahap pertama, melakukan koordinasi dan sosialisasi dengan pemerintah Desa Kersamenak, melakukan FGD, dan pengisian kuesioner awal. Tahap kedua adalah diskusi, dan tahap ketiga evaluasi melalui pengisian kuesioner akhir. Hasil evaluasi menunjukkan peserta memahami cara menentukan kesuburan tanah di lapangan dan cara mengidentifikasi hasil analisis tanah di laboratorium. Pemahaman peserta tentang cara menentukan kesuburan tanah secara langsung dan tidak langsung meningkat, dengan nilai post test untuk pengetahuan umum meningkat sebesar 21,72%. Pengetahuan tentang cara menentukan kesuburan tanah di lapangan meningkat 39,13%, dan pengetahuan  tentang  cara menentukan kesuburan tanah di laboratorium meningkat 26,09%. Kata Kunci: kesuburan tanah, produktivitas, sifat fisika, sifat kimia tanah